PENGARUH BAHAN AJAR BERBASIS FLIPBOOK PADA MATA PELAJARAN PENDIDIKAN PANCASILA MATERI NILAI-NILAI PANCASILA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS 5 SDN KEDENSARI 1 - Selvi Nuzululvia; Nurul Aini (Jurnal Muassis Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes and participation of fifth-grade students in Pancasila Education due to the use of conventional teaching materials that were less interactive and engaging. This study aimed to determine the effect of flipbook-based teaching materials on students’ learning outcomes and participation in Pancasila Education. This research employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample of this study consisted of 16 fifth-grade students of SDN Kedensari 1. Data collection techniques included tests to determine differences in learning outcomes before and after the treatment, as well as observation sheets to assess students’ participation during the learning process. Data analysis techniques included validity testing, reliability testing, normality testing, and t-test analysis. The results showed that the use of flipbook-based teaching materials had a significant effect on students’ learning outcomes. This was indicated by the increase in the average pretest score from 54.56 to 81.63 in the posttest. The t-test result showed a t-value of -7.548 with a significance value of 0.000 < 0.05 at a 5% significance level. In addition, students’ participation also improved, with 3 students (18.75%) categorized as very active and 13 students (81.25%) categorized as active. Therefore, it can be concluded that flipbook-based teaching materials significantly affected the learning outcomes and participation of fifth-grade students at SDN Kedensari 1 in Pancasila Education.